Trying to Survive: A Phenomenography of Ethno-Religion-Cultural-Based Family Business Management Resilience During Pandemic Situation - Rustam, Akie Rusaktiva; Narsa, I Made (Jurnal Aplikasi Manajemen, 2024)
This study focuses on the experiences and practices of owners/managers to capture and describe how owners/managers understand and practice business resilience during crisis (pandemic) situations within an Ethno-Religion Cultural-Based Family Business context. This paper provides new insights into the meaning and concept of business resilience from a cultural viewpoint, and about how a family business survives and keeps thriving during the crisis. This study applies phenomenography, an interpretive methodology, to bring to the surface the meaning and concept of business resilience understood and practiced by the owners/managers. In collecting data, the researcher conducts interviews with representatives (family members) of the two biggest family businesses in Surabaya, the second largest economy in Indonesia, with two different cultural settings. The researcher also conducts a review of the extant literature in the areas of resilience and families to obtain a deeper understanding. Firstly, family business is a complex interrelationship between complementary social-ecological systems. Second, this study finds that family business practices are determined by two qualitatively different views and understandings of resilience. This study provides a novel interpretation of resilience in the context of Ethno-Religion Cultural-Based Family Business and challenges the rationalistic approach by showing that the resilience concept is not universal but multifarious. The researcher acknowledges that literatures used are dominated by Western culture which is extremely different from Indonesian culture as lacks similar Indonesian literature.